Perubahan Prosesi Tradisi Balik Ulbas Pada Etnik Pakpak Di Desa Siempat Rube IV Kabupaten Pakpak Bharat - Ayu Assary Padang; Puspitawati Puspitawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation of the Balik Ulbas tradition and to analyze the factors that influence the changes to this tradition within the Pakpak community. This research uses a qualitative approach with a descriptive method. Research data were obtained through in-depth interviews, field observations, and documentation involving customary figures, community members who practice the tradition, and the younger generation in Resdes Village. All data were analyzed through the process of data reduction, data presentation, and conclusion drawing to obtain accurate and in-depth results regarding the phenomenon under study. This approach was chosen so that the researcher could comprehensively understand the cultural values and the forms of implementation of the Balik Ulbas tradition in the social life of the community. The results show that the Balik Ulbas tradition has undergone changes in its form of implementation caused by various factors, including technological advancements, changes in the mindset of the younger generation, and the influence of modernization and economics. These changes also affect the level of community participation in carrying out the customary tradition.